Embroidery with Smart Threads of some Saudi Folk Proverbs to Adorn Formal Women’s Clothing with the Art of one-line Calligraphy and Arabic Calligraphy - Elkherbawy, Randa Monier (Journal of natural sciences, life and applied sciences, 2022)
The importance of the research lies in the development of designs by merging some of the Saudi proverbs and writing them using one-line art and Arabic calligraphy and embroidering them automatically with smart (luminous) threads on official clothes and employing them to enrich the aesthetic values so that they represent the Saudi identity in official forums, and 10 designs were made Innovative, to add a new vision to women’s formal clothing, as it includes Saudi proverbs and drawing with the art of one newly developed calligraphy and Arabic calligraphy using smart (luminous) threads the research followed the descriptive experimental method by combining modernity in design and originality in choosing popular proverbs. The study tools were a questionnaire to evaluate the designs proposed by a number of arbitrators from specialized faculty members at King Khalid University. The results of the research came true to its hypotheses as follows 1- The possibility of integrating drawing with one-line art and writing in Arabic calligraphy some Saudi proverbs. 2-The possibility of using smart (luminous) threads to embroider on formal women’s clothing. 3-The possibility of achieving rhythm and proportion in the executed designs that suit official forums.